Kebijakan Pertanggungjawaban Pidana terhadap Pelaku Kelompok Kriminal Separatis Bersenjata (Studi Kasus Organisasi Papua Merdeka) - Ferdinand Sulteng; Setiyono Setiyono (MLJ Merdeka Law Journal, 2021)
The many years of conflict that occurred in Papua and Aceh in the past, must be seen epistemologically every incident that occurred in the area. There is a common thread in every conflict that occurs there, whether involving separatist movements or purely because of the dissatisfaction of the Papuan people due to legal products in the form of government policies and decisions issued for the area. It is not without reason that someone acts as a separatist against the state, as well as before the territory is declared out of the country, then legally all the people in the area still have rights that must be protected by the state. This means that before Papua leaves the territory of the Unitary State of the Republic of Indonesia, Papuans and separatists who live there are still Indonesian citizens and have the right to have their rights protected for Indonesia. The problems that will be investigated in this research are the Criminal Law Policy Against the Actors of the Armed Separatist Criminal Group and how is the criminal responsibility for the perpetrators of the Armed Separatist Criminal Group in Indonesia